2015
DOI: 10.3109/00016489.2015.1061697
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of concurrent chemoradiotherapy for locally advanced sinonasal squamous cell carcinoma: A single-institution study

Abstract: The locoregional recurrence-free, distant metastasis-free, disease-free, disease-specific, and overall survival rates did not differ between PORT and CCRT groups. In addition, there were no significant differences in incidence rates of acute and chronic toxicities between the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…All 44 studies included information on survival data, with 35 (n = 1903) reporting on 5-year OS. 4,6-8,10,11,14-18,23-55 The weighted mean overall 5-year OS in this review was 54.5% (range, 18%-75%). Five-year OS data available on all patients undergoing surgery, open and endoscopic surgery, no surgery, radiation, surgery alone, surgery and RT, CT, and CT and RT are reported in Table 3 .…”
Section: Resultsmentioning
confidence: 72%
“…All 44 studies included information on survival data, with 35 (n = 1903) reporting on 5-year OS. 4,6-8,10,11,14-18,23-55 The weighted mean overall 5-year OS in this review was 54.5% (range, 18%-75%). Five-year OS data available on all patients undergoing surgery, open and endoscopic surgery, no surgery, radiation, surgery alone, surgery and RT, CT, and CT and RT are reported in Table 3 .…”
Section: Resultsmentioning
confidence: 72%
“… 13 Conversely, Kim et al indicated no difference in survival rates between patients who underwent surgery and postoperative radiotherapy and those who received CCRT—including locoregional recurrence–free, distant metastasis–free, disease-specific, and overall survival. 14 …”
Section: Discussionmentioning
confidence: 99%
“…13 Conversely, Kim et al indicated no difference in survival rates between patients who underwent surgery and postoperative radiotherapy and those who received CCRT-including locoregional recurrence-free, distant metastasis-free, disease-specific, and overall survival. 14 There has been a consensus regarding multidrug therapy for several types of cancer, including leukemia, lymphoma, colon cancer, and lung cancer, considering action and resistance to drugs. One of the crucial reasons for failure of cancer treatment is the development of drug resistance by cancer cells; hence, multidrug therapy is a promising approach to prevent cancer cell resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Kreppel et al [ 18 ] published the results of 53 patients with locally advanced squamous cell carcinoma of the maxillary sinus and found a complete response rate of 21% after neoadjuvant CRT; higher response rates were seen with the use of cisplatin (10 of 11 patients with a complete response received cisplatin) [ 18 ]. However, despite the encouraging complete response rate, it is clear from other series of CRT alone that even with the administration of higher doses, a significant number of patients will ultimately fail loco-regionally [ 19 - 21 ]. Despite this, previous studies suggest patients who achieve a complete response after therapy appear to be in a better prognostic group than patients with a partial or stable response [ 5 ].…”
Section: Discussionmentioning
confidence: 99%